Radical acceptance: embracing your life with the heart of a Buddha - Brach, Tara (Bantam Books, 2003)
Foreword / Jack Kornfield -- Prologue: "Something is wrong with me" -- The trance of unworthiness -- Awakening from the trance: the path of radical acceptance -- The sacred pause: resting under the bodhi tree -- Unconditional friendliness: the spirit of radical acceptance -- Coming home to our body: the ground of radical acceptance -- Radical acceptance of desire: awakening to the source of longing -- Opening our heart in the face of fear -- Awakening compassion for ourselves: becoming the holder and the held -- Widening the circles of compassion: the bodhisattva's path -- Recognizing our basic goodness: the gateway to a forgiving and loving heart -- Awakening together: practicing radical acceptance in relationship -- Realizing our true nature.